مححدات نجاح اصحاب المؤسسات المصغرة المستفيدين من دعم اجهزة الدولة - الأوس هادي (البليدة2- كلية العلوم الإنسانية و الإجتماعية, 2025)
المنعم التعمير المحددات التي يملكها المقاولون الشباب المستفيدين من أحمد الدهم أهم المعايير والعوامل المساهمة على الجام المؤسسات المصغرة، وذلك لأهميتها في بقاء المؤسسات والشركات واستمراريتها، فالمقاول الذي لا يسعى إلى الرفع والقوية وتطوير وكلية محددات الغسية والشخصية والإقتصادية يكون مصير مؤسسته المثل والإضمحلال ومن ثم الزاول، في يمانية المحددات النفسية وقوة المحددات الشخصية وارتفاع الخدمات الاقتصادية تساعد المؤسسات على التكيف مع المغيرات المتعددة وبالتالي مواجهة التحديات يجميع أنواعها من الضخم، تغير في السياسات الحكومية والاستراتيجيات السياسية والدولية وعلى الأزمات الصحية، ناهيك من شده الله لة والآثار التي تعود على هذه المؤسسات الصغيرة، كما أن القليل صاحب كل هذه المحددات يوفر البدائل والحلول السرية لمختلف المشكلات التي يمكن أن تعترضه و تعارض مؤسسته او شركه بالإستناد على النموذج النظري المعارض، فإن هذه الدراسة استخدمت معطيات مستقاة من 172 مقول صاحب مؤسسة مصفرة مستفيد من اسمرة الدعم والتي تشكل عبيدة. امل اختبار المواج العربي أم الحميد الثانية (96) فرضيات وقياس مدى صدقها وتحققها، بحيث توضع . العرضيات والحمد طبيعة العلاقة والكثير من متغير المحددات النفسية الشخصية الاقتصادية الإجتماعية وسفير النجاح والعقل، كما تبحث عن وجود الفروق من المونتي الناجين والقشان لقد أوضحت المطالع إلى وجود تأثير خوبي دال إحصائياً بين كل من الأبعاد (سلولد المخاطرة، القدرات والإمكانيات، الثقافة المقاولاتية. الاتصالية التسويقية) الأفراد الحبيبة محل الدراسة وبين النجاح، كما كشفت الدراسة على وجود تثير متوسط مال إحصائياً بين كل من الأبعاد الانتماع والابتكار المواقف والإتجاهات المنافعية للإنجاز القيادات الأفراد العينة محل الفراسة وون النجاح، بالإضافة الي وجود تثير ضعيف دال إحصائياً بين كل من الأبعاد الإمكانيات المالية، القدرة النفسية) الأفراد العينة محل الدراسة وبين النجاح. كما خلصت الدراسة إلى عدم وجود تأثير نال إحصائياً بين كل من الأبعاد المتاح الإقتصادي، القدرة البشرية العاملة. الحبط الإجتماعي والمثلي الأفراد العينة محل الدراسة وبين النجاح كشفت الدراسة إلى وجود فروق ذات دلالة إحصائية بين المقاولين الناهين والفاشلين تبعاً للمحددات النفسية، ووعود فروق ذات دلالة إحصائية بين المقاولين الناجين والفاشلين تبعاً للمحددات الشخصية، ووجود فروق ذات دلالة إحصائية بين المقاولين الساعين والفاشلين تبعاً للمعددات الاقتصادية، إلا أن الدراسة لم تجد فروق ذات دلالة إحصائية بين المقاولين الناعمين والماشين بها المحددات الاجتماعية وقد التزمت الدراسة على أحمرة الدعم والمقلتين عليها المحددات الواجب أعذها بعين الإعتبار وقياسها قبل الشروع في عمالية المويل هذه المؤسسات المصغرة وهذا من أجل الرفع من إمكانية لتحقيق النجاح الاصحاب هذه المؤسسات، وبالتالي تسليم الفروض الأفراد منتسبين يكيم تعليق الراقي والإزدهار والعطور. الكليات الفلاحية المحددات المقاول، النجاح، الفشل، أحمرة الدم by young ontopes who berate for support devices we considered the most important criteria and factors contesting to the success of enterprises, due to their importance in the survival and continuity of institutions and comp. The who does not seek to case, strengthen, develop and grow his psychological detent will his institution fad, dechno and and tea cuppens. The positivity of psychological dataonica, the stongh of personal and the of dess help institutions adapt to emultiple changes and the dallenges of all kinds, from inflation, changes in gomet policies and political and international stategies, and won heath crises, not to mentan the inity of competition and the effects that affect these small enterprises. The who has all these determinants ako provides ativos and quick solutions problems that may confront him and his institution or company. Based on to the the bypassed thetical model, this mady and data obtained from 372 ontmpressums who own a call business and bonete for support devices, which consinee the research In code to the houstical mandel, eight (06) hypotheses www identified and their validity and vification www sand, sa but those hypotheses daily and don thereof the motionship and influence between the variable detoresinants (psychological, social, economic, social) and the varie of access and and the existence of differences between the two groups of sacces The read showed that the is a strong statistically úgráficas offct beach of the disies (idk be, capabilition and potential, entroproomaidd culture, maketing cocation) of the sample members under study and access. The study a ded a modete stitically gificant effect between each of the dimensions (creativity and ination,ades and treads, motivation to achieve, leadership) of the sample covetous under study and In addition, there is a weak statistically significant effect between ach of the diancial capabilities, competitive abilty) of the sample cavedess underland. The study also conceded that there is no muistically significa affect between sach of the domains (concenic dienst, human working capacity, soci d) of the sample under study and a The dyed the exence of statistically significat differs between succes and unsaccendied extrepreneurs according to psychological determinsets, the existence of tistically siguin differences between accordal and unsucceeded sempen according to pound determinas, and the nitence of minically significant dillenn between cand succostal verspeenous according to acceanic ditunicasts, but the study did not find meistically significare differences between accessed and unced tops according to social determinas. The sady sagged to the support agrees and those in charge of the the dents that cast be taken i condtion and sued bean sarting the process of founding those wire- enterprises in code to increase the posedilty of achieving access for the inations, and thus landing nor kuns to suitable individuals who can achieve of these advanceme, prosperity and develagenica.
Keywords: المؤسسات المصغرة; أجهزة الدعم; محددات النجاح; المقاولاتية; القيادة; المخاطرة